2004
DOI: 10.1074/jbc.m403197200
|View full text |Cite
|
Sign up to set email alerts
|

A Femtomolar Acting Octapeptide Interacts with Tubulin and Protects Astrocytes against Zinc Intoxication

Abstract: An octapeptide was previously described that protects neurons against a wide variety of insults directly and indirectly as a result of interactions (at femtomolar concentrations) with supporting glial cells. The current study set out to identify the octapeptide binding molecules so as to understand the high affinity mechanisms of cellular protection. Studies utilizing affinity chromatography of brain extracts identified tubulin, the brain major protein, as the octapeptide-binding ligand. Dot blot analysis with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
156
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 135 publications
(160 citation statements)
references
References 50 publications
4
156
0
Order By: Relevance
“…A similar colocalization of microtubules and the parathyroid hormone-related protein is involved in the transport of the latter into the nucleus (Lam et al, 2002). Recent studies have shown that the active peptide moiety of ADNP (NAP) interacts with tubulin (Divinski et al, 2004) to enhance cellular protection. Furthermore, NAP shares structural similarities with protein sequences that can penetrate the cell membrane at 4°C and at low pH, independent of a cellular receptor and are incorporated into cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar colocalization of microtubules and the parathyroid hormone-related protein is involved in the transport of the latter into the nucleus (Lam et al, 2002). Recent studies have shown that the active peptide moiety of ADNP (NAP) interacts with tubulin (Divinski et al, 2004) to enhance cellular protection. Furthermore, NAP shares structural similarities with protein sequences that can penetrate the cell membrane at 4°C and at low pH, independent of a cellular receptor and are incorporated into cells.…”
Section: Discussionmentioning
confidence: 99%
“…The gene that encodes ADNP is conserved in human, rat and mouse (∼90% homology). ADNP contains an eight-amino acid peptide sequence, NAPVSIPQ (termed NAP), which provides potent neuroprotection in vitro and in vivo (Bassan et al, 1999;Gozes et al, 2000a;Zamostiano et al, 2001;Alcalay et al, 2004;Divinski et al, 2004). Additionally, ADNP contains 9 zinc fingers, a homeobox domain profile, and a bipartite nuclear-localization signal, which indicate transcription factor activity (Zamostiano et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…At the microtubule level, single NAP molecules may amplify protein interaction at the level of the growing tip of the microtubule [23]. Furthermore, small NAP clusters may be associated with membrane pore formation, which may enhance NAP cellular uptake [4]. -1h, b -3h, c -24h.…”
Section: Study Of Nap Adsorption and Assembly On The Surface Of Hopgmentioning
confidence: 99%
“…Interest in the early steps of NAP self-assembly in aqueous media is largely due to its bioactivity at very low (sub-nanomolar) concentrations. A hypothesis to explain this activity is the formation of self-assembled structures that interact further with target molecules, either losing activity at high concentrations, or having to concentrate at the binding point [3]. This report investigates, using atomic force microscopy (AFM), whether NAP self-assembles into such macromolecular nanostructures at low concentrations at a wellcharacterized liquid-solid interface.…”
Section: Introductionmentioning
confidence: 99%
“…The parent protein, ADNP, is essential for brain development; it is found in the nuclei, cytoplasm, and occasionally along cytoplasmic microtubules [44,45]. In vitro studies showed that recombinant ADNP was found to protect neurons against severe oxidative stress [46].…”
Section: Nap Peptide Derived From Activitydependent Neuroprotective Pmentioning
confidence: 99%